Gembil (Game Ibu Hamil) Application Based On Android In Increasing Knowledge Of Primigravida During The Covid-19 Pandemic In 2022 - Lisnawati .; Rani Widiyanti; Pepi Hapitria (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
The existence of the Covid-19 pandemic has become one of the causes of changes in the health service order system, including one of the activities for pregnant women classes at health service facilities at the Puskesmas. The use of the internet has become a necessity in the last decade. Several studies also prove that the use of internet technology in social networking is effective in increasing knowledge, attitudes, perceptions, awareness and compliance in health. Therefore, the researchers tried to make the GEMBIL (Pregnant Mother Game) application. This study aims to produce a product in the form of the GEMBIL application (pregnant mother game) as an educational medium in the class of pregnant women, and to analyze the effect of using GEMBIL in increasing the knowledge of pregnant women about pregnancy, childbirth, postpartum and newborns. This is an analytical study with a quasi-experimental approach, using one group pre and post design. The research location is in the working area of ??the Majasem Public Health Center, Cirebon City. The sample uses purposive sampling. Bivariate analysis using Wilcoxon. the feasibility test of material experts showed a value of 84.7% and media experts showed a value of 83.3%. The relationship between the use of the GEMBIL application and knowledge, shows a significance value of 0.005 (p<0.05). The GEMBIL application is very feasible to be used as an appropriate technology medium in the implementation of online classes for pregnant women. There is a significant difference in knowledge between before and after attending an online class for pregnant women using the GEMBIL application.